Comparison of Performance of the Novel Chromogenic Spectra VRE Agar to That of Bile Esculin Azide and Campylobacter Agars for Detection of Vancomycin-Resistant Enterococci in Fecal Samples - Jenkins, S. G. (American Society for Microbiology, 2011)

(untitled)
A total of 142 stool specimens were evaluated for vancomycin-resistant enterococcus (VRE). Twenty-four-hour sensitivities and specificities, respectively, were 98% and 95% for Spectra VRE chromogenic agar (Remel, Lenexa, KS), 86% and 92% for bile esculin azide with vancomycin (BEAV; Remel), and 96.5% and 92% for Campylobacter agar (CAMPY; Remel). Spectra VRE and CAMPY are significantly more sensitive at 24 h than BEAV.